2010
DOI: 10.1186/1477-7525-8-109
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the DISABKIDS Chronic Generic Module (DCGM-37) when used in children undergoing treatment for cancer

Abstract: BackgroundThe aim was to evaluate data quality and psychometric properties of an instrument for measurement of health-related quality of life: DISABKIDS Chronic Generic Module (DCGM-37) used in school-aged children with cancer.MethodsAll school-children diagnosed with cancer in Sweden during a two-and-a-half year period were invited to participate in the study. Analysis was performed on combined data from two assessments, two and-a-half and five months after start of cancer treatment (n = 170). The instrument … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 17 publications
6
37
0
1
Order By: Relevance
“…Despite the fact the instrument discriminated between gender (proxy version) and age (self version) groups, effect sizes were larger for discrimination between conditions. These findings have been observed in previous studies (Sandeberg, Johansson, Hagell, & Wettergren, 2010), and emphasize the adequacy of DISABKIDS-37 to discriminate between diagnoses (the original main purpose of the instrument), without rejecting its sensitivity to age specificities. Levels of agreement between parent/caregiver and child/adolescent reports were only moderate in our study, besides the fact that evidence on the discriminant validity of the questionnaires was differently observed in each report form.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Despite the fact the instrument discriminated between gender (proxy version) and age (self version) groups, effect sizes were larger for discrimination between conditions. These findings have been observed in previous studies (Sandeberg, Johansson, Hagell, & Wettergren, 2010), and emphasize the adequacy of DISABKIDS-37 to discriminate between diagnoses (the original main purpose of the instrument), without rejecting its sensitivity to age specificities. Levels of agreement between parent/caregiver and child/adolescent reports were only moderate in our study, besides the fact that evidence on the discriminant validity of the questionnaires was differently observed in each report form.…”
Section: Discussionsupporting
confidence: 85%
“…The fact that every facet's internal consistency was always higher than its correlation to the other facets suggests that facet scores depict distinct aspects of paediatric HRQL; however, the suggested factorial structure is to be tested in further studies since the ones 16 conducted so far reported inconsistent findings (Sandeberg, Johansson, Hagell, & Wettergren, 2010;Schmidt et al, 2006). Regarding convergent validity, the fact that moderate to strong associations were observed between generic QL and HRQL instruments underlines the pertinence of assuming those two concepts as complementary in their applications, but somehow distinct in nature (Wallander, Schmitt, & Koot, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As has been reported in several studies (Dean et al, 2010;Abdel Hai, Taher, & Fattah, 2010;Farnik et al, 2010), it is well established that children with chronic conditions have significant impairments in HRQoL. As expected, self-reported scores for overall HRQOL of cancer children were more impaired than those of healthy children (Eiser, Eiser, & Stride, 2005;Sung et al, 2009;Sandeberg, Johansson, Hagell, & Wettergren, 2010;Varni, Limbers, & Burwinkle, 2007). School functioning was most impacted by chronic health conditions, as reflected by the higher rates of school absences (Dean et al, 2010), and quit of school.…”
Section: Cancer Childsupporting
confidence: 68%